Development and Validation of Multiplex Quantitative PCR Assay for Detection of Helicobacter pylori and Mutations Conferring Resistance to Clarithromycin and Levofloxacin in Gastric Biopsy [Corrigendum] - Binmaeil H; Hanafiah A; Mohamed Rose I; Raja Ali RA (Infection and Drug Resistance, 2023)
Binmaeil H, Hanafiah A, Mohamed Rose I, Raja Ali RA. Infect Drug Resist. 2021;14:4129–4145. The authors have advised that Table 1 on page 4132 is incorrect. There is an error in the clarithromycin resistant gene reverse primer and UreA probe sequences. The authors apologize for these errors. The correct Table 1 is as follows.